PEMASARAN POLITIK BASYIR PADA PEMILIHAN UMUM KEPALA DAERAH KOTA PEKALONGAN TAHUN 2010 - Sinaga, Rudi Salam (Universitas Medan Area, 2014)
Regional head candidates hoping to appear as an elected regional heads in local elections (Election) with regional heads so each candidate will do various forms of business activities in the market including their political ideas by Bashir-mate Alex the regional head election (Election) Pekalongan in 2010 The purpose of this study to determine the political marketing used in the election of Bashir Pekalongan. The method used qualitative descriptive type using interview techniques and literature. These results indicate that the figure Bashir has had since the beginning of social capital as a doctor and a social being so generous in the use of political marketing Bashir form no trouble.